2022
DOI: 10.1155/2022/5085183
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Improves Keratinocyte Proliferation, Inflammation, and Oxidative Stress through Mediating the SPAG5/FOXM1 Axis in an In Vitro Model of Actinic Dermatitis by Ultraviolet

Abstract: Background. Chronic actinic dermatitis (CAD) is an abnormally proliferating photoallergic skin disease. Dysregulated inflammation and oxidative stress are the immediate factors in the abnormal proliferation of keratinocytes. This study aimed to investigate the effect of curcumin on the aberrant proliferation of keratinocytes in an in vitro (actinic dermatitis) AD model and the possible molecular mechanisms. Methods. The keratinocytes were irradiated with ultraviolet (UV) to construct an in vitro AD model and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In this transcriptomic study, we describe an abundance of changes occurring in the heart after UUO that comprise a broad spectrum of biological processes. Among them, we identified other UUO-upregulated cardiac genes ( Birc5, Cd300E, Foxm1, Spag5, Hmmr, Dach1, Akap5, and Yes1 ) that could advance our understanding of the relationship between kidney disease and cardiac dysfunction due to their involvement in immune responses, cardiac repair, fibrosis, inflammation, proliferation, oxidative stress, and apoptosis [ [30] , [31] , [32] , [33] ]. These genes could provide novel insights into CKD-related cardiac pathways contributing to CRS progression though their direct contribution needs to be validated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…In this transcriptomic study, we describe an abundance of changes occurring in the heart after UUO that comprise a broad spectrum of biological processes. Among them, we identified other UUO-upregulated cardiac genes ( Birc5, Cd300E, Foxm1, Spag5, Hmmr, Dach1, Akap5, and Yes1 ) that could advance our understanding of the relationship between kidney disease and cardiac dysfunction due to their involvement in immune responses, cardiac repair, fibrosis, inflammation, proliferation, oxidative stress, and apoptosis [ [30] , [31] , [32] , [33] ]. These genes could provide novel insights into CKD-related cardiac pathways contributing to CRS progression though their direct contribution needs to be validated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time that the essential roles of CYPs family with oxidative stress and immune responses were connected with the pathological process of IDD, which were worth of subsequent in-depth research. Existed studies have reported the essential roles of MMPs family and their inhibitors screening in the progression of IDD, among which MMP1 may participate partially through OS-related functions and inflammatory reactions ( 61 , 62 ). NQO1 served as antioxidant genes and played essential roles in ameliorating inflammatory responses, reticulum stress, and apoptosis of degenerative NP cells, which were partially regulated by the antioxidant transcription factor Nrf2 ( 14 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Photodermatoses, also known as disorders of cutaneous photosensitivity, encompass a diverse array of inflammatory skin conditions that are triggered or exacerbated by exposure to solar radiation. 1 , 2 Among these, chronic actinic dermatitis (CAD) is a rare, persistent immunological photodermatosis that manifests as a pruritic eczematous eruption on sun-exposed skin when subjected to ultraviolet (UV) light, 3 , 4 encompassing both ultraviolet A and ultraviolet B, as well as visible light, 5 accompanied by the development of papules and lichenified plaques. 6 In severe cases, it can progress to erythroderma with palmoplantar hyperkeratosis, 7 and in some instances, it can transform into cutaneous lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Currently, no curative treatment for CAD. 5 Topical calcineurin inhibitors (TCIs) and topical and systemic corticosteroids are first-line pharmacological management options. In severe cases, indicated systemic immunosuppression usually involves cyclosporine, methotrexate, mycophenolate mofetil, and azathioprine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation